Far Eastern Cultural Tourism as a Factor of Influence on Undergraduate Museum Studies - A. V. Alepko (Высшее образование в России, 2018)
The article addresses the problem of undergraduate training in the field of cultural tourism, excursion activities and museology in the Far Eastern region of Russia. The author focuses on the features of the tourism sector development in Khabarovsk territory. A brief description of the archaeological collection of one of the most attractive Museums for tourists – the Khabarovsk Regional Museum of Local Lore is given. The article dwells on the content and features of the disciplines included in the curriculum of bachelors majoring in «Museology», taking into account the geographical location, socio-economic development and cross-cultural communications of the region. The author emphasizes the importance of historical and Museum studies in Russian and in regional education. The article comes to a conclusion that undergraduate training in the field of cultural tourism and excursion activities is in the coming decades quite a promising area of activity of the Khabarovsk State Institute of Culture.